2004
DOI: 10.1128/jvi.78.17.9412-9422.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus (EBV) SM Protein Induces and Recruits Cellular Sp110b To Stabilize mRNAs and Enhance EBV Lytic Gene Expression

Abstract: Promyelocytic leukemia protein (PML) nuclear bodies or nuclear domain 10s (ND10s) are multiprotein nuclear structures implicated in transcriptional and posttranscriptional gene regulation that are disrupted during replication of many DNA viruses. Interferon increases the size and number of PML nuclear bodies and stimulates transcription of several genes encoding PML nuclear body proteins. Moreover, some PML nuclear body proteins colocalize at sites of viral DNA synthesis and transcription. In this study, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…2B). Since CMV promoter activity is not affected by SM (47,61), these results indicate that SM could actually enhance accumulation of BHRF1 mRNA posttranscriptionally, similar to its effect on the majority of EBV transcripts (25). Nevertheless, since the net effect of SM on BHRF1 expression during EBV replication was inhibitory, it appeared likely that SM inhibits the activity of the BHRF1 promoter in the EBV genome during lytic replication.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…2B). Since CMV promoter activity is not affected by SM (47,61), these results indicate that SM could actually enhance accumulation of BHRF1 mRNA posttranscriptionally, similar to its effect on the majority of EBV transcripts (25). Nevertheless, since the net effect of SM on BHRF1 expression during EBV replication was inhibitory, it appeared likely that SM inhibits the activity of the BHRF1 promoter in the EBV genome during lytic replication.…”
Section: Resultsmentioning
confidence: 76%
“…The BHRF1 gene contains an intron 5Ј to the single open reading frame, suggesting the possibility that SM inhibited BHRF1 expression posttranscriptionally (51). In addition, SM has not been shown to inhibit transcription when its effects on transcription have been directly examined by nuclear run-on assays (47,61). We therefore asked whether SM would inhibit BHRF1 expression when the intron-containing gene was transcribed from a heterologous promoter.…”
Section: Resultsmentioning
confidence: 99%
“…SM is thought to bind to EBV mRNAs in the nucleus and to enhance mRNA export by recruiting cellular export factors (3,7,18). In addition, SM enhances the nuclear accumulation of target mRNAs, suggesting that SM also increases RNA stability (28,35). SM binds to mRNA targets in vivo, which can be coimmunoprecipitated with SM (33).…”
mentioning
confidence: 99%
“…In addition, it has been shown that PML-NBs have role in the repression of HSV-1 infection in the absence of functional ICP0 and they may be involved in regulating lytic and latent infection of HSV-1 (Wang et al, 2012). PML-NB protein has been shown to interact with the EBV protein SM and increase the stability of lytic EBV transcripts (Nicewonger et al, 2004). In addition, PML has been among three hub genes identified by Network analysis showing significant differential expression between EBV positive and negative post-transplant lymphoproliferative disorder (PTLD).…”
Section: 8019 Promyelocytic Leukemia Gene Functions and Roles In Tummentioning
confidence: 99%